Kajian Hidrogeomorfologi Mataair di Sebagian Lereng Barat Gunungapi Lawu - Langgeng Wahyu Santosa (Universitas Muhammadiyah Surakarta, 2006)
Magma activities on earth surface cause dynamic of volcanic morphology from the volcanic cone up to fluvial volcanic plain. The changing of morphology is always followed by different slope, composition and thickness of material, and break of slope. This geomorphological conditions result in groundwater emerges forming spring belt. Accordingly, wether such phenomena are also the case in the west slope of Lawu volcano is investigated in this reseach. Hydrogeomorphology approach is applied to study of the spring characteristic and distribution in the research area. The result research shows that the distribution pattern of springs in the west slope of Lawu volcano is not like spring belt perfectly, like the strato volcano generally. It is caused by erosion processes, mass wasting intensively, Lawu fault and other faults. Most springs flow on the volcanic slope and volcanic foot morphology.